Aboard the helicopter: from adult science to early years (and back). Issue 1 (2nd January 2020) - Watts, Mike; Salehjee, Saima
ABSTRACT: This paper links early foundations in science for young children to the eventual achievement of science literacy for adults. There are five key arguments being made: (i) the early-years foundation stage (EYFS) specialists need to have a view for exactly what foundations are being laid in classrooms; (ii) that they all need to be – minimally – scientifically literate, despite the variety of definitions of that term; (iii) becoming scientifically literate is a long-term process of engaging with and developing an interest in 'matters scientific' that are easily available in the public domain; (iv) that there is a plethora of informal learning opportunities in science across the UK to foster adult engagement, and (v) taking a 'helicopter view' on occasions helps shape planning and processes in the nursery/ reception school classroom. To illuminate this, we offer two examples from materials science that grow out of traditional block play, and from all things plastic.